Radical prostatectomy in T4 prostate cancer after inductive androgen deprivation: results of a single‐institution series with long‐term follow‐up. (7th June 2018) - Hajili, Turkan; Ohlmann, Carsten H.; Linxweiler, Johannes; Niklas, Christina; Janssen, Martin; Siemer, Stefan; Stoeckle, Michael; Saar, Matthias
Abstract : Objectives: To determine the outcomes of complete surgical resection of T4 prostate cancer after inductive androgen‐deprivation therapy (ADT), as inductive ADT and subsequent radical prostatectomy (RP) is not recommended by any guideline yet. Patients and Methods: A monocentric RP database was queried for patients initially diagnosed with T4 prostate cancer, considered primarily as inoperable because of a fixed mass defined by rectal examination in combination with high PSA level and/or large foci of biopsy confirmed undifferentiated prostate cancer. Treatment consisted of primary ADT until PSA nadir with consecutive RP. Patients underwent retropubic RP (RRP) or robot‐assisted laparoscopic RP (RALP) after inductive ADT until achievement of the PSA nadir, which is in general reached after 6–7 months. The intraoperative course and complications were analysed. Finally, Kaplan–Meier estimates were calculated for overall survival (OS) and prostate cancer‐specific survival (PCSS). Results: We retrospectively identified 116 patients treated between 2000 and 2014. At diagnosis, the median (range) PSA level was 37.6 (2.44–284) ng/mL. The preoperative median (range) PSA after inductive ADT was 0.73 (0.01–34) ng/mL. Thereafter, patients underwent RRP or, since 2006, RALP. The median (95% confidence interval) OS was 156 (118.9–193.1) months. The PCSS at 150 months was 82%. Conclusions: Surgical therapy of primarily inoperable prostate cancer is feasible and safe after inductive ADT. The OS of this cohort seems comparable with results described for patients with primary operable high‐risk prostate cancer.